Kontroversi Pemikiran Abdul Rauf Al-Singkili - Syamzan Syukur (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2015)
This writing explored how was the thought of Abdul Rauf al-Singkili who lived in the 17th century. One of his intellectual position was his voiceless on the women leadership. As it was noted that Aceh Sultanate had been ever ruled by four Sultanah (women ruler), respectively till the end of 17th century, and Abdul Rauf was trusted as qadhi at the time. Abdul Rauf was considered controversial in the field of theology and mystics. He wanted to balance between syariah and hakikat (mystical philosophy). He was expert in hadis, tafsir and tasauf, thus brought him to be well known as the 17th Muslim intellectual.